2023
DOI: 10.7759/cureus.42954
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Tumor Shrinkage Following Enfortumab Vedotin Therapy for Metastatic Urothelial Carcinoma After Radical Cystectomy With Neoadjuvant Chemotherapy: A Case Report

Abstract: A 39-year-old Japanese male patient presented with a chief complaint of gross hematuria persistent for two months. However, no relevant findings in the patient’s medical and family history were observed. He was diagnosed with muscle-invasive bladder cancer, clinical stage T2bN0M0. After four courses of neoadjuvant chemotherapy with gemcitabine and cisplatin, the tumor size reduced by approximately 30%. The patient underwent robot-assisted radical cystectomy with standard lymph node dissection followed by intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although a 59.1% decrease in nectin-4 expression was observed in the metastatic biopsy, it showed a 19.1% increase relative to the nectin-4 expression in the primary lesion, indicating the difference in EV efficacy between primary and metastatic lesions [7]. Namiki et al reported that the tumor shrinkage effect differed by metastatic sites treated with EV therapy [8]. They also suggested that treatment strategies to overcome resistance to EV are required.…”
Section: Discussionmentioning
confidence: 99%
“…Although a 59.1% decrease in nectin-4 expression was observed in the metastatic biopsy, it showed a 19.1% increase relative to the nectin-4 expression in the primary lesion, indicating the difference in EV efficacy between primary and metastatic lesions [7]. Namiki et al reported that the tumor shrinkage effect differed by metastatic sites treated with EV therapy [8]. They also suggested that treatment strategies to overcome resistance to EV are required.…”
Section: Discussionmentioning
confidence: 99%